2000
DOI: 10.1554/0014-3820(2000)054[1313:rcdasi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Character Displacement and Speciation in Periodical Cicadas, With Description of a New Species, 13-Year Magicicada Neotredecim

Abstract: Abstract. Acoustic mate‐attracting signals of related sympatric, synchronic species are always distinguishable, but those of related allopatric species sometimes are not, thus suggesting that such signals may evolve to “reinforce” premating species isolation when similar species become sympatric. This hypothesis predicts divergences restricted to regions of sympatry in partially overlapping species, but such “reproductive character displacement” has rarely been confirmed. We report such a case in the acoustic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
140
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(148 citation statements)
references
References 48 publications
7
140
1
Order By: Relevance
“…Male cicadas produce airborne calling songs that signal mating availability to females. Calling songs thus function as species specific mate recognition signals (Dugdale & Fleming, ; Marshall & Cooley, ; Cooley & Marshall, ; Gogala & Trilar, ; Sueur & Aubin, ; Marshall et al ., ; Gogala, ) that can be used to separate species faster than morphological or molecular differences (Popple et al ., ; Marshall et al ., ; Popple, ; Nunes et al ., ; Hertach et al ., ). Song differences often precede morphological differentiation (Hill et al ., ; Marshall et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Male cicadas produce airborne calling songs that signal mating availability to females. Calling songs thus function as species specific mate recognition signals (Dugdale & Fleming, ; Marshall & Cooley, ; Cooley & Marshall, ; Gogala & Trilar, ; Sueur & Aubin, ; Marshall et al ., ; Gogala, ) that can be used to separate species faster than morphological or molecular differences (Popple et al ., ; Marshall et al ., ; Popple, ; Nunes et al ., ; Hertach et al ., ). Song differences often precede morphological differentiation (Hill et al ., ; Marshall et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In some systems, shifts in female preferences may subsequently select for additional divergence in male secondary sexual traits that facilitate species recognition (e.g., Saetre et al 1997). In fact, geographic variation in receiver selectivity has been assessed in a growing number of recent studies that have provided various degrees of empirical support for reproductive character displacement (Gerhardt 1994(Gerhardt , 1999Noor 1995;Marquez and Bosch 1997;Saetre et al 1997;Rundle and Schluter 1998;Pfennig 2000;Marshall and Cooley 2000;Gabor and Ryan 2001).…”
mentioning
confidence: 99%
“…Grant (1972) identified a number of practical difficulties in detecting character displacement, including the difficulty in distinguishing true displacement caused by the presence of another species from variation caused by adaptation to environmental variables. Although reproductive character displacement has been demonstrated in a number of species (Bordenstein et al 2000;Kulathinal and Singh 2000;Marshal Simon et al 2000; but see Noor et al 2000), only a few have clearly demonstrated a role for selection in this divergence. These include Drosophila (Higgie et al 2000), flycatchers (Saetrre et al 1997(Saetrre et al , 1999, sticklebacks (Hatfield and Schluter 1996;Hatfield 1997;Rundle and Schluter 1998), whitefish (Bernatchez et al 1996;Pigeon et al 1997;Lu and Bernatchez 1998), and ground crickets ).…”
mentioning
confidence: 99%